2018
DOI: 10.1088/1361-6501/aae234
|View full text |Cite
|
Sign up to set email alerts
|

Vision-based system for long-term remote monitoring of large civil engineering structures: design, testing, evaluation

Abstract: This paper presents a full research and development cycle of a vision-based system for long-term remote monitoring of civil engineering constructions. To measure displacements, the system analyzes reference mark position using a developed image processing algorithm. All computational operations are performed by FPGA to ensure high performance. The developed monitoring system has an accuracy of 0.45 mm (3 standard deviations) at the distance up to 50 m. The measurement error remains within this value even in ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…e climatic, environmental, economic, and sociopolitical challenges within civil projects make it di cult in digitization within the construction industry. Since last decade, computer-based monitoring systems and simulations using image processing, AI, ML, and others have piqued the interest among civil engineering community as a cost-e ective and unobtrusive solution for image and video data collection and analysis in many construction organizations [1][2][3][4][5][6][7][8][9][10][11][12][13]. As a result, several applications were targeted by previous researchers in 3D imaging technologies for construction management, progress monitoring [9,10], safety [14], and quality control [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…e climatic, environmental, economic, and sociopolitical challenges within civil projects make it di cult in digitization within the construction industry. Since last decade, computer-based monitoring systems and simulations using image processing, AI, ML, and others have piqued the interest among civil engineering community as a cost-e ective and unobtrusive solution for image and video data collection and analysis in many construction organizations [1][2][3][4][5][6][7][8][9][10][11][12][13]. As a result, several applications were targeted by previous researchers in 3D imaging technologies for construction management, progress monitoring [9,10], safety [14], and quality control [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A measurement system consisting of a single objective lens and CMOS multimatrix has a strong anti-interference ability, and it is easier to install temperature control, humidity control, IR filters, and other devices inside the system to calibrate the impact of environmental changes on the measurement accuracy. Therefore, the accuracy of the system measurement in a complex environment such as a wide temperature range, rain, and snow climate is guaranteed [18]. The above characteristics provide the basic experimental support for the engineering design proposed in this study.…”
Section: Experimental Base Unit Setupmentioning
confidence: 75%
“…To improve the accuracy of the measurement, the FPGA needs to capture 30 frames from the CMOS multi-matrix and calculate the average value to determine the coordinates of the image. The information-processing algorithm and FPGA parameters of the measurement unit mentioned in this study can be found in [14], [18]. Then the frame grabber is used and the image coordinate information is transmitted to the data analysis computer through the CMOS multi-matrix interface RS-485.…”
Section: Base Unit Schemementioning
confidence: 99%
“…In addition to the image total station, some related infrastructure-monitoring applications combine laser ranging and vision. Vasileva et al [ 98 ] proposed a monitoring system similar to the image total station, but different from the total station. The laser and camera of this system were not coaxial, and a heating device was added to monitor the infrastructure displacement at a low temperature.…”
Section: Vision–laser-based Infrastructure Monitoringmentioning
confidence: 99%